2002
DOI: 10.1590/s0034-70942002000300003
|View full text |Cite
|
Sign up to set email alerts
|

Raquianestesia com a mistura enantiomérica de bupivacaína a 0,5% isobárica (S75-R25) em crianças com idades de 1 a 5 anos para cirurgia ambulatorial

Abstract: com a Mistura Enantiomérica de Bupivacaína a 0,5% Isobárica (S75-R25) em Crianças com Idades de 1 a 5 Anos para Cirurgia Ambulatorial Justificativa e Objetivos -A bupivacaína comercialmente u t i l i z a d a a p r e s e n t a -s e c o m o m i s t u r a r a c ê m i c a RS(±)bupivacaína. Embora o enantiômero levógiro S(-)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
3
0
3
Order By: Relevance
“…Most surgeries were performed under general anesthesia and one may consider that all children were submitted to this type of anesthesia; in some cases, however, the anesthesiologist has associated general to epidural or local anesthesia 11 . Anesthesia duration varies according to surgery length, and the anesthetic level varies according to surgery complexity and length and, since each body reacts differently to anesthetic drugs, anesthesia duration may also vary, even in cases of surgeries of the same size 3,12 . Our study has shown broad variation on anesthesia time, between 25 and 200 minutes, with prevalence of 45 to 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeries were performed under general anesthesia and one may consider that all children were submitted to this type of anesthesia; in some cases, however, the anesthesiologist has associated general to epidural or local anesthesia 11 . Anesthesia duration varies according to surgery length, and the anesthetic level varies according to surgery complexity and length and, since each body reacts differently to anesthetic drugs, anesthesia duration may also vary, even in cases of surgeries of the same size 3,12 . Our study has shown broad variation on anesthesia time, between 25 and 200 minutes, with prevalence of 45 to 60 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Levobupivacaine in proportions of 75% levorotatory and dextrorotatory 25% was obtained in 1997 9 . It was marketed in isobaric solution and used in adults 10 and children 11 . In 2009, 50% enantiomeric excess bupivacaine was used in 0.4% hyperbaric solution in different volumes with excellent results in infraumbilical procedures 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Embora não tenha havido grupo controle os resultados desse estudo foram favoráveis quando se considerou a duração de ação e a eficácia do bloqueio motor. (Imbelloni et al, 2002).…”
Section: Limitações Do Estudounclassified